Analysis Of Liquidity Ratio To Financial Performance at PT. Duta Intidaya Tbk - Wulandari, Fitri; Wulan A, A. Bidari Chandra; Idris, Hariany (Universitas Negeri Makassar, 2023)
This research aims to determine the cause of the decrease and increase in the company's ratio, and to determine and analyze the liquidity ratio to the financial performance of PT. Duta Intidaya Tbk for 2019 to 2020This type of research is descriptive, with the object of research is the financial statements of PT. Duta Intidaya Tbk. With the type of quantitative data and secondary data sources. Where in research in analyzing financial performance by using liquidity ratios, namely the current ratio and cash ratio.The results showed that the financial performance of PT. Duta Intidaya Tbk has increased and decreased in accordance with the effectiveness of the standard, this can be seen from the calculation of the liquidity ratio that has been carried out has increased and decreased and this resulted in the company is still in good condition. and the decrease in the liquidity ratio occurred due to the company's ability to pay its short-term debt or to cover some of its assets and cash, the current ratio decreased from 2019 to 2020 by 68.39% and the cash ratio increased by 16.79%.